Addressing Women's Unmet Health Care Needs in a Canadian Remand Center: Catalyst for Improved Health?. (July 2018) - Besney, Jonathan D.; Angel, Cybele; Pyne, Diane; Martell, Rebecca; Keenan, Louanne; Ahmed, Rabia
Incarcerated women have a disproportionate burden of infectious and chronic disease, substance disorders, and mental illness. This study explored incarcerated women's health and whether a Women's Health Clinic improved care within this vulnerable population. Retrospective chart reviews and focus groups were conducted. Poor access to care in the community due to competing social needs was described. Barriers to care during incarceration included lack of comprehensive gender-specific services, mistrust of providers, and fragmentation. Of 109 women, high rates of mental illness, partner violence, substance use, sexually transmitted infection (STI), and irregular Pap testing were observed. Pap (15% to 54%, p < .001) and STI (17% to 89%, p < .001) testing rates increased. Fragmentation of care remained at transition points, and further work is needed to improve continuity within corrections and the community.